Hubungan Dukungan Sosial dengan Kesepian pada Narapidana Dewasa Awal Lajang - Grace Ayunita Batara; Sri Aryanti Kristianingsih (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
This study aims to determine the relationship between social support and loneliness in early single adult prisoners. The subjects in this study was an early single adult convict of 30 people 18-40 years of age. Data were analyzed using correlation product moment from Karl Pearson. The calculation method is assisted by using the SPSS program. The results of this study indicate that there is a negative relationship between social support and loneliness (r = -0.357, p = 0.026). The magnitude of the influence of social support variables on loneliness is 12.8% while the remaining 87.2% is influenced by other variables. This means, the higher the social support, the lower the loneliness of early adult inmates, and vice versa, the lower the social support, the higher the loneliness of early adult prisoners to be single. Researchers are expected to be able to develop other factors that influence the variable loneliness inmates such as gender and socioeconomic status.